Childhood pheochromocytoma in a survivor of central primitive neuroectodermal tumor. Issue 4 (5th August 2013) - Nakano, Yoshiko; Fujimaru, Rika; Ishii, Keiichi; Sakamoto, Hiroaki; Inoue, Takeshi; Sako, Masahiro; Yamada, Hiroshi
Abstract: Pheochromocytoma and central nervous system primitive neuroectodermal tumor are both neural crest‐derived tumors. The former is usually benign and develops mainly in adulthood and the latter brain tumor mainly occurs in childhood and has a poor prognosis. We report a case of a 15‐year‐old boy who developed pheochromocytoma after more than 10 years of complete remission of central primitive neuroectodermal tumor. Thus far, there have been no reports of childhood cancer survivors who developed pheochromocytoma. This quite rare occurrence of two tumors in a single patient may imply some unidentified linkage or common genetic background.